From floating to dirigisme - Heiko Körner (Intereconomics, 1971)
The test case of “flexible versus fixed rates of exchange” has now been running for four months. Experience in this transitional and incipient phase has shown up a number of faults and impediments which are typical not only of the problems created by contemporary multicentric international economic policies but also of the kind of difficulties facing German economic policy in particular.
Keywords: 330; International Monetary Policy